2011
DOI: 10.4314/ejc.v3i2.63613
|View full text |Cite
|
Sign up to set email alerts
|

Needs Assessment of Guidance Services in Schools as a Method for Achieving Quality Education in Nigeria: An Exploration Study

Abstract: The researchers conducted this study in order to establish a case for the use of needs assessment of guidance services as a means of achieving quality education in Nigeria. They contacted 84 professional counsellors in Ilorin, a typical Nigerian metropolis, in order to gather data on their perception of the importance of certain guidance services in secondary schools. They also determined the actual level of services rendered in schools. The instrument used for collecting the necessary data was titled "Guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Among wives, their own accommodation was associated with marital quality, supporting previous work (Johnson et al, 2005; Rusbult et al, 1991, 1996), while no such effect was found for husbands. Previous examinations in Islamic countries demonstrated that good communication and problem-solving were associated with increased perceived marital happiness, satisfaction, and stability among married men and women (Al-Othman, 2012; Askari et al, 2012; Esere et al, 2011). In the present study, unlike the others, we examined couples and analyzed partner effects rather than just actor effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among wives, their own accommodation was associated with marital quality, supporting previous work (Johnson et al, 2005; Rusbult et al, 1991, 1996), while no such effect was found for husbands. Previous examinations in Islamic countries demonstrated that good communication and problem-solving were associated with increased perceived marital happiness, satisfaction, and stability among married men and women (Al-Othman, 2012; Askari et al, 2012; Esere et al, 2011). In the present study, unlike the others, we examined couples and analyzed partner effects rather than just actor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Greater marital quality is associated with various positive factors and better individual and family functioning, including better health (Robles et al, 2014; Whisman et al, 2014), higher life satisfaction, happiness and subjective well-being (Carr et al, 2014), reduced spousal loneliness (Stokes, 2017), and greater parenting quality (Carlson et al, 2011). In accordance, many researchers have examined factors that influence marital quality, including personal factors and communication within couples (Askari et al, 2012; Esere et al, 2011; Litzinger & Gordon, 2005).…”
Section: Marital Qualitymentioning
confidence: 99%
“…Guidance is defined as a set of cognitive educational services that use accurate, reliable and valid information to help students understand themselves (Esere, 2020). In this study, guidance services refers to all the guidance activities, namely counselling, appraisal, information, consultation, placement, referral and orientation services, which the school undertakes to meet the academic, financial, placement, personal and social needs of students.…”
Section: Introductionmentioning
confidence: 99%
“…Effective guidance services can be used to reduce the negative impacts of such issues on the lives of students, and improve their well-being (Martin et al, 2015). Counselling services have been shown to be effective in treating psychological distress in a wide range of situations (Bani et al, 2020).Guidance is defined as a set of cognitive educational services that use accurate, reliable and valid information to help students understand themselves (Esere, 2020). In this study, guidance services…”
mentioning
confidence: 99%
See 1 more Smart Citation